Railway crane platform stabilization system - D. A. Potakhov (Вестник Научно-исследовательского института железнодорожного транспорта)
When operating a railway crane in curved sections of the track, derailment of wheelsets of the crane bogies from the rail track when it is displaced during hanging on the outriggers, wheelset of the bogie missing the rail track after the work has been completed or the crane has been down from the outriggers, which significantly affects performance of loading and unloading operations. One of the reasons for the occurrence of such dangerous situations is the not strictly horizontal position of the non-rotating platform of the railway crane.Railway cranes are part of recovery trains designed to eliminate the consequences of rolling stock derailments. A priority for recovery trains is to reduce the time it takes to eliminate the consequences of traffic accidents, which can be achieved through the use of new or improved devices or methods.The article describes a system of automatic stabilization (leveling) of the platform of a railway crane (for example, EDK 500/1 crane type) when it moves in curved sections of the track (the motion of a railway crane at relatively low speeds (up to 50 km/h) is considered).In order to study the modernized technical system (a crane equipped with an automatic platform stabilization system), its mathematical simulation is carried out. At the initial stage, a solidstate digital model of a railway crane in combination with a section of a railway track is created in the SolidWorks computer-aided design system; developed solid model is translated into the Sim- Mechanics MATLAB environment. Further, in order to improve the adequacy of modeling, the developed dynamic model is being finalized by integrating MATLAB program libraries (SimMechanics, SimHydraulics, Fuzzy Logic Toolbox, etc.) to take into account the interaction of elements of different physical nature. Results of modeling modernized technical system are presented, which confirm the advisability of using the stabilization system on railway cranes when passing curved track sections.